THE ROLE OF LEADERSHIP, CORPORATE CULTURE REINFORCEMENT, AND HUMAN CAPITAL DIVISION IN PREVENTING FRAUD STUDY ON ISLAMIC BANKS - Ade Yuliar; Dita Andraeny (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
The rapid growth of Islamic Banking in Indonesia raises the risk of fraud as happened in Islamic Bank X in the last few years, in which the trend continues to increase. This study aims to unravel the root of fraud problem in Islamic Banking and strive to provide appropriate solutions in the prevention of fraud through qualitative approach. This study provides a formulation of role model and leadership policy through the reinforcement of organizational culture and the role of Human Capital Division as a step in the prevention of fraud.